RANCANG BANGUN APLIKASI PERENCANAAN PENGELOLAAN KEBUTUHAN BAHAN BAKU PADA PDAM SURYA SEMBADA KOTA SURABAYA - Amirulloh, Nur; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
Abstract: Local drinking water company which later can be abbreviated PDAM according to the mayor (200 ) is a company belonging to local government that move in the field of drinking water services. PDAM has a duty to pursue the provision of drinking water that meets the terms of health care for people in the city of surabaya and surrounding areas. The problems that occur on PDAM Surya Sembada of surabaya city difficulty in optimize the cost of supplies and economical determine orders to the needs of production. This is because the process of planning supplies raw materials done with see the need of raw materials for the production for a year be submitted to a section of supplies at the end of the current year, insufficient production needs in reality in the next year. Where as all raw materials required for the production of Â order done once a year by auction supplier , then raw materials will be sent to PDAM every month.Of the existing problems then required raw materials management planning application needs taps on PDAM Surya Sembada of surabaya city that can help in making planning senior managers supplies of raw materials .This application applies the methods of Triple Exponential Smoothing Winter, Re-Order Point (ROP), and Economic Order Quantity (EOQ). Through this method planning raw materials produced needs to suit the needs accurate production line. In the step of experiment try and evaluation, this research produce raw materials management planning application needs taps on solar system sembada city surabaya. It can be seen than average on a page control supervisor supplies are 4.2, the average conformity on a page planning supervisor supplies are 4.5, the average conformity on a page is 4.3 production supervisor, the average manager conformity on a page supplies are 4.5, and the average senior managers conformity on a page supplies and provision is 4.4. The one generated by the application of the accuracy with the kind of having microsoft excel. This application can be developed with the complement of the security system,use mobile platform, and equipped functional report notifikasi delivery via email and via sms a gateway.